Exploring Cultural Diversity in Indonesia: Models, Responses, and Multicultural Politics - Acim, Acim; Subagja, Dita Jelia; Afiani, Diva Ayu; Pratama, Georgy Rio; Al Kautsar, Fathan (Candidate: Jurnal Sains Politik, 2023)
ReligiosityÂ isÂ aÂ thingÂ inÂ whichÂ thereÂ areÂ manyÂ differencesÂ thatÂ growÂ andÂ emergeÂ inÂ socialÂ life,Â ofÂ courseÂ thisÂ diversityÂ isÂ aÂ commonÂ thing,Â becauseÂ itÂ isÂ certainÂ thatthisÂ diversityÂ arisesÂ andÂ developsÂ soÂ thatÂ humansÂ canÂ respectÂ eachÂ other,Â andÂ ofcourseÂ soÂ thatÂ communityÂ groupsÂ canÂ liveÂ sideÂ byÂ sideÂ withoutÂ seeingÂ anydifference.Â OfÂ course,Â theÂ challengeÂ thatÂ mustÂ beÂ facedÂ isÂ regardingÂ pluralismÂ ormustÂ beÂ ableÂ toÂ acceptÂ everyÂ differenceÂ thatÂ exists.Â BecauseÂ asÂ weÂ allÂ knowÂ thateachÂ groupÂ mustÂ haveÂ itsÂ ownÂ uniqueÂ culturalÂ characteristicsÂ orÂ customs,Â whichcanÂ beÂ saidÂ toÂ beÂ difficultÂ orÂ veryÂ difficultÂ toÂ understandÂ andÂ influencedÂ byÂ otherculturesÂ andÂ groups.Â OfÂ course,Â differencesÂ inÂ diversityÂ bothÂ inÂ termsÂ ofÂ religion,Â ethnicity,Â culture,Â language,Â andÂ nationÂ areÂ certainlyÂ somethingÂ thatÂ inevitablymustÂ beÂ acceptedÂ togetherÂ in orderÂ toÂ buildÂ multiculturalismÂ in orderÂ toÂ createjustice,Â peace,Â andÂ tolerance.